2006
DOI: 10.1186/cc5053
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock is correlated with asymmetrical dimethyl arginine levels, which may be influenced by a polymorphism in the dimethylarginine dimethylaminohydrolase II gene: a prospective observational study

Abstract: Introduction Asymmetrical dimethyl arginine (ADMA) is an endogenous non-selective inhibitor of nitric oxide synthase that may influence the severity of organ failure and the occurrence of shock secondary to an infectious insult. Levels may be genetically determined by a promoter polymorphism in a regulatory gene encoding dimethylarginine dimethylaminohydrolase II (DDAH II), which functions by metabolising ADMA to citrulline. The aim of this study was to examine the association between ADMA levels and the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 25 publications
4
40
2
Order By: Relevance
“…18 It has been suggested that DDAH2 may also play a role in both the physiological regulation of the cardiovascular system and also in the pathophysiological response to sepsis. 13 This is the first study to demonstrate a physiological role for DDAH2 and shows that knockout of the enzyme results in an animal with mild hypertension seen during periods of activity that is associated with elevated methylarginine concentrations and reciprocal reductions in systemic NO levels. This study also shows for the first time that in polymicrobial sepsis, Ddah2 deletion has a profound impact on NO production, immune function, and outcome, and it is macrophage DDAH2 that is a key regulator of this effect.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…18 It has been suggested that DDAH2 may also play a role in both the physiological regulation of the cardiovascular system and also in the pathophysiological response to sepsis. 13 This is the first study to demonstrate a physiological role for DDAH2 and shows that knockout of the enzyme results in an animal with mild hypertension seen during periods of activity that is associated with elevated methylarginine concentrations and reciprocal reductions in systemic NO levels. This study also shows for the first time that in polymicrobial sepsis, Ddah2 deletion has a profound impact on NO production, immune function, and outcome, and it is macrophage DDAH2 that is a key regulator of this effect.…”
Section: Discussionmentioning
confidence: 84%
“…The DDAH2 gene is found in the major histocompatibility complex III region 16 and polymorphisms of the promoter region of the gene have been shown to affect circulating ADMA levels and illness severity in both adult and pediatric populations with severe sepsis, 13,14 however, the small number of subjects examined in these studies necessitates cautious interpretation of these data. Given these associations, we went on to explore the functional role of Ddah2 in sepsis using highly specific genetic modifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations